Design and rationale of the Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy (MR RESCUE) Trial. Issue 1 (13th September 2012) - Kidwell, Chelsea S.; Jahan, Reza; Alger, Jeffry R.; Schaewe, Timothy J.; Guzy, Judy; Starkman, Sidney; Elashoff, Robert; Gornbein, Jeffrey; Nenov, Val; Saver, Jeffrey L.; ,
<x xml:space="preserve">Abstract</x> Rationale Multimodal imaging has the potential to identify acute ischaemic stroke patients most likely to benefit from late recanalization therapies. Aims The general aim of the Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy Trial is to investigate whether multimodal imaging can identify patients who will benefit substantially from mechanical embolectomy for the treatment of acute ischaemic stroke up to eight‐hours from symptom onset. Design Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy is a randomized, controlled, blinded‐outcome clinical trial. Population studied Acute ischaemic stroke patients with large vessel intracranial internal carotid artery or middle cerebral artery M1 or M2 occlusion enrolled within eight‐hours of symptom onset are eligible. The study sample size is 120 patients. Study intervention Patients are randomized to endovascular embolectomy employing the Merci Retriever (Concentric Medical, Mountain View, CA) or the Penumbra System (Penumbra, Alameda, CA) vs. standard medical care, with randomization stratified by penumbral pattern. Outcomes The primary aim of the trial is to test the hypothesis that the presence of substantial ischaemic penumbral tissue visualized on multimodal imaging (magnetic resonance imaging or computed tomography) predicts patients most likely to respond to mechanical embolectomy for treatment of acute ischaemic stroke due to a large vessel, intracranial occlusion up to eight‐hours from symptom onset. This hypothesis will be tested by analysing whether pretreatment imaging pattern has a significant interaction with treatment as a determinant of functional outcome based on the distribution of scores on the modified Rankin Scale measure of global disability assessed 90 days post‐stroke. Nested hypotheses test for (1) treatment efficacy in patients with a penumbral pattern pretreatment, and (2) absence of treatment benefit (equivalency) in patients without a penumbral pattern pretreatment. An additional aim will only be tested if the primary hypothesis of an interaction is negative: that patients treated with mechanical embolectomy have improved functional outcome vs. standard medical management.